Efficacy and patient tolerability of travoprost BAK-free solution in patients with open-angle glaucoma and ocular hypertension - Sophia K Mirza (Dove Medical Press, 2010)
Sophia K Mirza, Sandra M JohnsonDepartment of Ophthalmology, University of Virginia, Charlottesville, Virginia, USAAbstract: The medical treatment of glaucoma has evolved significantly over the past several decades. The main driving forces behind this evolution are the safety profiles and efficacy of these medications. Prostaglandin (PG) analogs are shown to be superior to older drugs in both efficacy and tolerability. Though there are much fewer side effects that manifest after using PG analogs, the adherence and compliance to medication regimens are surprisingly lower than expected. A commonly sited reason is the ocular irritation and inflammation with these medications. Much of this inflammation can be attributed to the preservative, benzalkonium chloride (BAK). The chronic clinical and subclinical inflammation becomes increasingly detrimental when filtration surgery fails from bleb fibrosis secondary to this hypercellularity. A BAK-free formulation of a PG analog recently became available. BAK-free travoprost is reviewed here. It has demonstrated equal efficacy and less ocular surface toxicity than its preserved counterparts. It is expected to serve as an instrumental resource in managing ocular hypertension and glaucoma in patients who demonstrate significant sensitivity to BAK. More randomized, controlled, double-blind studies are encouraged to evaluate its improved safety and tolerability.Keywords: glaucoma, benzalkonium chloride, Travatan Z, sofZia